Using WEDPI learning package to upgrade teacher's skills on information technology - Johan Eddy Luaran; Sabariah Sharif; Zulkifli Mohamed (IGI Global, 2013)
The change in teaching techniques which applies information technology brings about a paradigm shift in our country's educational system. However, past researches have shown that the application of information technology in classrooms is still at an unsatisfactory level. This is caused by a group of teachers who haven't been able to master the basic skills of information technology application even after attending the courses. Therefore, the purpose of this research is to determine the level of skillfulness of primary school teachers - especially those in the interiors - on information technology, and thereafter develop a multimedia learning package (WEDPI Package for Learning) which will hopefully assist these weak teachers to increase their level of skillfulness in information technology. WEDPI refers to the productivity tools, which includes applications for word-processing (Microsoft Word), electronic spreadsheet (Microsoft Excel), database (Microsoft Access), presentation (Microsoft PowerPoint) and the Internet. This research adopted the quantitative approach and the ADDIE model was used in the development of this multimedia learning package. To obtain information on the level of skillfulness, the researcher carried out a hands-on test. The pre-experimental designs, which are the pre-test and post-test, were executed to determine if there were any difference in the level of skillfulness of the teachers after using the WEDPI Package for Learning. The research findings showed that teachers involved gave positive comments about the experience in using this stand alone learning material. The respondents also stated that the WEDPI Package for Learning is easy to use, flexible and is able to help them increase their level of skills in information technology. This is supported by the t-test results which show that there is a significant difference in the achievement of teachers' scores.